2020
DOI: 10.1371/journal.pone.0241849
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mechanical device-related complications in tube fed patients: A multicenter prospective cohort study

Abstract: Aims To identify the types of nasogastric/nasoenteric tube (NGT/NET)-related adverse events and to analyze the degree of harm and the factors associated with mechanical device-related complications. Materials and methods A prospective cohort study was conducted from October 2017 to April 2019 in seven Brazilian hospitals. Data from 447 adult patients with NGT/NET were collected through electronic forms. Three methods were used to assess the NGT/NET-related adverse events: (1) encouraging spontaneous reports;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
(58 reference statements)
0
7
0
11
Order By: Relevance
“…The loss of the enteral tube and accidental extubation are events that occur, most of the time, during the execution of the bed bath performed by the nursing team ( 4 , 17 , 18 , 25 ) . Critically ill patients are four times more likely to have enteral tube-related AEs compared to patients receiving minimal care ( 5 , 25 ) . Thus, the nursing dimensioning shall be adequate to the care need identified in the unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of the enteral tube and accidental extubation are events that occur, most of the time, during the execution of the bed bath performed by the nursing team ( 4 , 17 , 18 , 25 ) . Critically ill patients are four times more likely to have enteral tube-related AEs compared to patients receiving minimal care ( 5 , 25 ) . Thus, the nursing dimensioning shall be adequate to the care need identified in the unit.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nursing dimensioning shall be adequate to the care need identified in the unit. Furthermore, the use of an evidence-based care protocol can help reduce these adverse events ( 2 , 3 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This poses two significant challenges to the development of a safe infusion protocol: optimizing the delivery rate depending on the site of placement of the infusion tube (post-vs. pre-pyloric), and minimizing and preventing retrograde flow from the stomach into the esophagus, which could result in aspiration into the airways and subsequent pneumonia/pneumonitis [20][21][22]. The latter is still to date one of the most significant risks related to enteral feeding of critically ill patients, which motivates the need for novel technologies to monitor the placement of the enteral feeding tube and prevent and control reflux [23][24][25]. Thus, the protocol was optimized with the goal of minimizing (and possibly eliminating) the possibility of reflux from the intestine and stomach into the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…1 A multicentre survey conducted in seven hospitals across four regions of Brazil found that accidental loss and tube obstruction were the most common mechanical incidents in adult patients receiving enteral nutrition. 2 These incidents are often attributed to professionals' lack of knowledge about best practices in dose preparation and administration, as well as inadequate training and equipment for correct medication preparation. 3 Reducing tube obstruction rates should be a priority for healthcare institutions, as such incidents increase costs and the risk of negative outcomes for patients.…”
Section: Introductionmentioning
confidence: 99%